Pengaruh Kemasan Produk Dan Daya Tarik Iklan Terhadap Minat Beli Rokok Djarum Bla (Studi Kasus Konsumen Rokok Djarum Black Di Kabupaten Lahat) - Tri Rusilawati Kasisariah; Hayani Hayani; Hestin Hestin; Saparudin Saparudin (Journal of Innovative and Creativity, 2025)
The title of this research is "The Influence of Product Packaging and Advertising Attractiveness on Interest in Buying Djarum Black Cigarettes (Case Study of Djarum Cigarette Consumers in Lahat City)". The objectives of this research include: to determine the influence of product packaging on consumer interest in buying Djarum Black cigarettes in Lahat City, to determi ne the influence of advertising appeal on consumer interest in buying Djarum Black cigarettes in Lahat City and to determine the influence of product packaging and attractiveness. joint advertising on the interest in buying Djarum Black cigarettes among consumers in Lahat City. The sample for this research is 75 Djarum Black cigarette consumers in Lahat City. This research uses quantitative research, using data sources including: primary data, secondary data, population and sample. The data collection methods used were: observation, interviews and distributing questionnaires to a number of respondents. As well as using validity and reliability measuring instruments, prerequisite analysis tests, then using data analysis methods using multiple regression analysis, hypothesis testing in the form of t tests and F tests, as well as correlation coefficients and coefficients of determination. Data analysis in this research used SPSS 23.0. From the results of this research, it can be seen partially with the t test that the product packaging variable with t calculated > from t table or 5.503> 2.000, is rejected, accepted, this shows that there is a significant influence between product packaging and purchasing interest. So the hypothesis in this research is proven. The advertising attractiveness variable with t calculated > from t table or 4.573 > 2.000, then H_0 is rejected, H_a is accepted, this shows that there is a significant influence between advertising attractiveness on purchasing interest. So the hypothesis in this research is proven. From the results of the F test, the test decision is Ho rejected, Ha accepted because F count > F table, namely 302.471 > 2.72 and the significant value < 0.005, namely 0.000, then the decision taken is rejected, accepted, meaning that together the product packaging and Overall advertising attractiveness has a significant influence on purchasing interest. So the hypothesis in this research is proven